OIL RESERVES ANALYSIS IN BATANG FIELD WITH MATERIAL BALANCE METHOD FOR PRESSURE MAINTENANCE - Fachri Muhammad Winant; Suranto Suranto; Boni Swadesi (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
Material Balance method is a concept of material equilibrium with measurement of response from reservoir (pressure) due to production, injection, and influx activities so that it can calculate the appropriate Original Oil in Place. By creating a material balance model, it can be done the development plan of Batang Field with the aim of obtaining cumulative optimum oil production. Batang Field is still feasible to be developed using pressure maintenance scenarios seen from OOIP of 144.3 MMSTB, Recovery Factor of 14.9% and Current Pressure of 70-80 psi. Pressure Maintenance is a water injection with the aim of replacing the fluid that has been produced so that it is expected to keep the reservoir pressure from falling. Ideally this method requires Voidage Replacement Ratio (VRR) = 1 as the target injection. Economic calculation using Cost Recovery from this scenario shows a positive NVP ( 2,865,000 USD). Therefore, development projects using Pressure Maintenance can be applied in the field. With this paper, it is hoped that it can increase reserves and lifespan of the Batang oil field.